CYTOTOXICITY OF FIVE PLANT EXTRACTS AGAINST DIFFERENT HUMAN CANCER CELL LINES AND THEIR MOLECULAR MECHANISM - EL-HALLOUTY, SALWA; BATAWI, ASHWAQ; SHAFI, MANAL; RASHWAN, ESAM; ELHAWARY, EZZELDIN; ABDELAAL, NESMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Five methanol plant extracts namely, Euphorbia hierosolymitana, Dracaena marginata, Cordyline terminalis, and Sapium sebifera were screened in vitro for their cytotoxic effect on human tumor cell lines; namely, PC-3, HepG-2, HCT-116, and MCF-7 (prostate, liver, colon, and breast cancer) and human normal cell lines, namely, BJ-1. Methods: E. hierosolymitana (extract A) selectively inhibited HCT-116 cell proliferation with IC50 of 4.22 μg/ml, both Dracaena marginata (extract B) (bark, leaves, and branches) showed moderate cytotoxicity on MCF-7 with IC50 of 22.4 and 48.2 μg/ml, respectively. The remaining two extracts showed minimal to insignificant percentage inhibition on all cell lines. Results: E. hierosolymitana extract was selected for further studying, where the effect of the extract on the HCT116 cells showed a downregulation of her2 and Bcl-2 gene and overexpression of the Bax gene. Flow cytometry analysis was also performed to understand the effect of E. hierosolymitana on the apoptosis induction and the cell cycle. The results showed the induction of early and late apoptosis by 5.81 and 10.01%, respectively. Conclusion: Our results infer that E. hierosolymitana has a promising chance in fighting colorectal cancer due to its high cytotoxic effects on HCT116 cancer cells while having minimal effects on the BJ-1 normal cell lines.